Whole genome sequencing puts forward hypotheses on metastasis evolution and therapy in colorectal cancer - Ishaque, Naveed; Abba, Mohammed L.; Patil, Nitin; Paramasivam, Nagarajan; Hübschmann, Daniel; Leupold, Jörg; Balasubramanian, Gnana Prakash; Kleinheinz, Kortine; Toprak, Umut; Hutter, Barbara; Benner, Axel; Kerssemakers, Jules; et al. (Nature Communications, 2018)
The evolution and genetic nature of metastatic lesions is not completely characterized. Here the authors perform a comprehensive whole-genome study of colorectal metastases in comparison to matched primary tumors and define a multistage progression model and metastasis-specific changes that, in part, are therapeutically actionable.
Gesehen am 19.02.2020